Hybrid HVDC circuit breaker with self-powered gate drives - Effah, Francis Boafo; Watson, Alan James; Ji, Chao; Amankwah, Emmanuel K.; Johnson, Christopher Mark; Davidson, Colin; Clare, Jon C. (IET, 2016)
The ever increasing electric power demand and the advent of renewable energy sources have revived the interest in high-voltage direct current (HVDC) multi-terminal networks. However, the absence of a suitable circuit breaker or fault tolerant VSC station topologies with the required characteristics (such as operating speed) have, until recently, been an obstacle in the development of large scale multi-terminal networks for HVDC. This paper presents a hybrid HVDC circuit breaker concept which is capable of meeting the requirements of HVDC networks. Simulation results are presented which are validated by experimental results taken from a 2.5kV, 700A rated laboratory prototype.